Shaping Virtual Retail: Identifying Key Influences in Metaverse Shopping with Fuzzy DEMATEL - Lekhika Sharma; Neeraj Kaushık (Journal of Metaverse, 2025)
The Metaverse is significantly transforming e-commerce by providing immersive and interactive virtual shopping environments. This study explores the qualitative aspects and user interactions that shape customer experiences on Metaverse platforms. The research uses the Fuzzy DEMATEL (FDEMATEL) technique to identify and prioritize 11 key factors influencing digital shopping experiences, derived from literature and expert opinions. The FDEMATEL approach effectively examines causal relationships among these factors, reducing the bias associated with imprecise human judgments. The study reveals that flow, immersion, and ease of use are prominent factors, while informativeness, media richness, and risk are critical cause factors for successful retail platforms. These findings offer valuable insights for managers and platform developers to enhance Metaverse shopping experiences. The study uniquely identifies and analyzes the causal relationships of critical success factors, providing a comprehensive understanding that can drive the success of Metaverse retail environments.